Formula: y = mx + b
m being the slope
Slope given: -2, plug it in
Y = -2x + b
Now find y intercept (b)
Plug in the point (5,-11)
-11 = -2(5) + b
-11 = -10 + b, b = -1
Solution: y = -2x -1
Answer 6 dollars and 52 cents
Step-by-step explanation: 6 1/4 = (6.25)
40.75/6.25 = 6.52 per unit price
Answer:
B. 0.602%
Step-by-step explanation:
Probability is essentially (# times specific event will occur) / (# times general event will occur). Here, we have a few specific events: draw a quarter, draw a second quarter, draw a penny, and draw another penny. The general event will just be the number of coins there are to choose from.
The probability that the first draw is a quarter will be 4 / (4 + 8 + 9) = 4/21.
Since we've drawn one now, there's only 21 - 1 = 20 total coins left. The probability of drawing a second quarter is: (4 - 1) / (21 - 1) = 3/20.
The probability of drawing a penny is: 9 / (20 - 1) = 9/19.
The probability of drawing a second penny is: (9 - 1) / (19 - 1) = 8/18.
Multiply these four probabilities together:
(4/21) * (3/20) * (9/19) * (8/18) = 864 / 143640 ≈ 0.602%
The answer is B.
Answer: $56
Step-by-step explanation:
Divide 24 by 3 to get 8
$8 will be the amount it'll cost for 1 t-shirt
So you would multiply 7 by 8 to get 56
So $56 will be the amount of 7 t-shirts
Answer:
The solved given expression is
![\frac{-4}{7}+\frac{2}{7}x-14x+\frac{4}{7}=\frac{-96x}{7}](https://tex.z-dn.net/?f=%5Cfrac%7B-4%7D%7B7%7D%2B%5Cfrac%7B2%7D%7B7%7Dx-14x%2B%5Cfrac%7B4%7D%7B7%7D%3D%5Cfrac%7B-96x%7D%7B7%7D)
Step-by-step explanation:
Given expression is ![\frac{-4}{7}+\frac{2}{7}x-14x+\frac{4}{7}](https://tex.z-dn.net/?f=%5Cfrac%7B-4%7D%7B7%7D%2B%5Cfrac%7B2%7D%7B7%7Dx-14x%2B%5Cfrac%7B4%7D%7B7%7D)
To solve the given expression :
![\frac{-4}{7}+\frac{2}{7}x-14x+\frac{4}{7}](https://tex.z-dn.net/?f=%5Cfrac%7B-4%7D%7B7%7D%2B%5Cfrac%7B2%7D%7B7%7Dx-14x%2B%5Cfrac%7B4%7D%7B7%7D)
![=\frac{-4+4+2x}{7}-14x](https://tex.z-dn.net/?f=%3D%5Cfrac%7B-4%2B4%2B2x%7D%7B7%7D-14x)
![=\frac{0+2x}{7}-14x](https://tex.z-dn.net/?f=%3D%5Cfrac%7B0%2B2x%7D%7B7%7D-14x)
![=\frac{2x}{7}-14x](https://tex.z-dn.net/?f=%3D%5Cfrac%7B2x%7D%7B7%7D-14x)
![=\frac{2x-14x(7)}{7}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B2x-14x%287%29%7D%7B7%7D)
![=\frac{2x-98x}{7}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B2x-98x%7D%7B7%7D)
![=\frac{-96x}{7}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B-96x%7D%7B7%7D)
Therefore ![\frac{-4}{7}+\frac{2}{7}x-14x+\frac{4}{7}=\frac{-96x}{7}](https://tex.z-dn.net/?f=%5Cfrac%7B-4%7D%7B7%7D%2B%5Cfrac%7B2%7D%7B7%7Dx-14x%2B%5Cfrac%7B4%7D%7B7%7D%3D%5Cfrac%7B-96x%7D%7B7%7D)
Therefore the solved given expression is
![\frac{-4}{7}+\frac{2}{7}x-14x+\frac{4}{7}=\frac{-96x}{7}](https://tex.z-dn.net/?f=%5Cfrac%7B-4%7D%7B7%7D%2B%5Cfrac%7B2%7D%7B7%7Dx-14x%2B%5Cfrac%7B4%7D%7B7%7D%3D%5Cfrac%7B-96x%7D%7B7%7D)